2020
DOI: 10.3390/s20051465
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Building Extraction Method from High Spatial Resolution Remote Sensing Images Based on Improved Mask R-CNN

Abstract: In this paper, we consider building extraction from high spatial resolution remote sensing images. At present, most building extraction methods are based on artificial features. However, the diversity and complexity of buildings mean that building extraction methods still face great challenges, so methods based on deep learning have recently been proposed. In this paper, a building extraction framework based on a convolution neural network and edge detection algorithm is proposed. The method is called Mask R-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 23 publications
1
43
0
1
Order By: Relevance
“…The Joanópolis building dataset is also complex; for example, it can have two instances under the same roof, which represents a reality in the field but a difficult or impossible case to resolve by the algorithm. Because the most recent works using Mask R-CNN to segment building instances are applied to different datasets [11,12], unfortunately, accuracies are not compatible with our results and comparison of the different methods on the same datasets will be made in a future work.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The Joanópolis building dataset is also complex; for example, it can have two instances under the same roof, which represents a reality in the field but a difficult or impossible case to resolve by the algorithm. Because the most recent works using Mask R-CNN to segment building instances are applied to different datasets [11,12], unfortunately, accuracies are not compatible with our results and comparison of the different methods on the same datasets will be made in a future work.…”
Section: Discussionmentioning
confidence: 84%
“…For example, the Mask R-CNN algorithm, which is probably the most widely used method nowadays, consists of two distinct modules: the first module is Faster R-CNN [10], which attributes a label to the object and generates the bounding box to encapsulate the object, while the second module produces a mask of the object [6]. The most recent published works focusing on building instance segmentation have used Mask R-CNN and shown that it performs poorly for edge extraction and to preserve the integrity of the building instances [11,12]. The second method is based on the prediction of the the mask characteristics to further segment the instance in a posterior step.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with edge detection technology, convolutional neural networks can effectively deal with the recognition and segmentation of complex buildings [28].…”
Section: Related Workmentioning
confidence: 99%
“…Ji and Lu (2019) proposed a novel FCN based Siamese architecture and tested the architecture using their dataset which contains images from different sources. Zhang et al (2020) improved the building extraction efficiency of wellknown deep learning model Mask R-CNN using Sobel edge detection algorithm.…”
Section: Introductionmentioning
confidence: 99%